Low-shrinkage 3D printing light-cured resin and preparation method thereof
By introducing spirocyclic orthocarbonate and composite zinc oxide whiskers into the photocured 3D printing resin and using self-healing polyurethane, the problems of poor strength and high shrinkage in the prior art are solved, and low shrinkage is achieved. High strength and self-healing 3D printed resin.
Patent Information
- Application Number
- CN202411351269.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2025-02-11
AI Technical Summary
In the existing photocuring 3D printing technology, high crosslinking and uneven polymer networks lead to poor product strength and high shrinkage, limiting the application of photocuring 3D printing.
Self-healing polyurethane was prepared by using biphenyl diols containing DA structures and hydrophobic benzophenone derivatives and ultrasonic mixing with other ingredients under a nitrogen atmosphere to prepare a low shrinkage 3D printed photocuring resin. The resin introduces spirocyclic orthocarbonate as the expansion monomer and adds composite zinc oxide whiskers to improve performance.
It realizes the low shrinkage, high strength, good waterproof and stain resistance, UV resistance and self-repairability of photocuring resin, and improves the overall performance of 3D printed products.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the field of resin technology, in particular to a low-shrinkage 3D printing photocurable resin and a preparation method thereof. Background Art
[0002] With the development of society, the market share of photocuring 3D printing with high efficiency and fast molding speed is constantly increasing. Therefore, the precision requirements for photocuring 3D printed products are also getting higher and higher. As one of the raw materials for photocuring 3D printing, the performance of photosensitive resin directly affects the printing speed and product performance.
[0003] In the existing photocuring 3D printing process, problems such as poor strength and high shrinkage due to high cross-linking and uneven polymer networks are often encountered, which greatly limits the application of photocuring 3D printing. Summary of the invention
[0004] The object of the present invention is to provide a low-shrinkage 3D printing photocurable resin and a preparation method thereof, so as to solve the problems in the prior art.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: A method for preparing a low-shrinkage 3D printing photocurable resin comprises the following steps: S1: Preparation of self-healing polyurethane using biphenyl diols containing DA structure and hydrophobic benzophenone derivatives; S2: In a nitrogen atmosphere, an initiator, a diluent, a self-healing polyurethane, bisphenol A epoxy acrylate, dipropylene glycol diacrylate, a composite zinc oxide whisker, and a spirocyclic orthocarbonate are ultrasonically mixed and stored away from light to obtain a low-shrinkage 3D printing photocurable resin.
[0006] Furthermore, the diluent is prepared by mixing isobornyl acrylate and 1,6-hexanediol diacrylate in a mass ratio of 1:1.
[0007] Furthermore, the initiator is a cationic initiator and a free radical initiator mixed in a mass ratio of 2:1.
[0008] Furthermore, the raw material composition of the photocurable resin is, by weight: 10-15 parts of bisphenol A epoxy acrylate, 10-15 parts of dipropylene glycol diacrylate, 14-16 parts of self-healing polyurethane, 0.5-1 parts of initiator, 12-17 parts of diluent, 2-5 parts of composite zinc oxide whiskers, and 2 parts of spirocyclic orthocarbonate.
[0009] Further, the preparation of the spirocyclic orthocarbonate comprises the following steps: In a nitrogen atmosphere, trimethylolpropane allyl ether and toluene are mixed, heated to 115°C and kept warm for 2 hours, cooled to 68-72°C, p-toluenesulfonic acid is added, cooled to 25-35°C, tetraethyl orthocarbonate is added, heated to 113-115°C and kept warm for 3-4 hours, cooled to 25-35°C, triethylamine is added, distilled under reduced pressure, dried, and purified by silica gel chromatography using a mixture of petroleum ether and ethyl acetate in a volume ratio of 9:1 as an eluent to obtain spirocyclic orthocarbonate.
[0010] Further, the preparation of composite zinc oxide whiskers comprises the following steps: 1) Mix deionized water, anhydrous ethanol, formic acid and 3-methacryloxypropyltrimethoxysilane, add zinc oxide whiskers, heat to 98-100°C and keep warm for 3-4 hours, centrifuge, wash and dry to obtain pretreated zinc oxide whiskers; 2) Under a nitrogen atmosphere, hydroxyethyl methacrylate, glycidyl methacrylate, pretreated zinc oxide whisker, vinyl POSS, azobisisobutyronitrile, and N,N-dimethylformamide are mixed, heated to 63-68° C. for 8-10 hours, deionized water is added, and dried to obtain an intermediate preparation; 3) Mix the hydrophobic benzophenone derivative, the intermediate preparation and chloroform, add Amberlyst-15 ion exchange resin, stir ultrasonically, heat to 55-65°C in a water bath for 2-3 hours, filter and rotary evaporate to obtain composite zinc oxide whiskers.
[0011] Furthermore, the preparation of the self-healing polyurethane comprises the following steps: (1) Under a nitrogen atmosphere, biphenyl bismaleimide and 1,4-dioxane are mixed, heated to 58-62°C, stirred until dissolved, furfuryl alcohol is added, kept warm for 22-24 hours, cooled, ether is added, filtered, washed, and dried to obtain a biphenyl diol containing a DA structure; (2) Under a nitrogen atmosphere, isophorone diisocyanate, polytetrahydrofuran and dibutyltin dilaurate are mixed, the temperature is raised to 63-68°C, a mixture of biphenyl diol containing a DA structure and acetone is added, the temperature is kept for 2-3 hours, a mixture of pentaerythritol triacrylate and acetone is added, the temperature is kept for 1-2 hours, a hydrophobic benzophenone derivative and 4-methoxyphenol are added, the temperature is kept for 1-2 hours, the temperature is lowered to 25-35°C, triethylamine is added, the temperature is kept for 20-30 minutes, and the material is discharged by rotary evaporation to obtain a self-healing polyurethane.
[0012] Furthermore, the mass ratio of isophorone diisocyanate, polytetrahydrofuran, biphenyl diol containing DA structure, pentaerythritol triacrylate, and hydrophobic benzophenone derivative is 16:8:2.4:5:3.
[0013] Furthermore, the preparation of the hydrophobic benzophenone derivative includes the following steps: under a nitrogen atmosphere, 4-hydroxybenzophenone and N,N-dimethylformamide are mixed, 2-bromoethanol, potassium carbonate, and N,N-dimethylformamide are added, the temperature is raised to 78-82°C and kept warm for 22-24 hours, rotary evaporation, extraction with dichloromethane and saturated brine in turn, anhydrous magnesium sulfate is added to remove water, suction filtration, rotary evaporation, and purification by silica gel column chromatography using petroleum ether and ethyl acetate in a volume ratio of 4:1 as eluent, rotary evaporation, and drying to obtain a hydrophobic benzophenone derivative.
[0014] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a low-shrinkage 3D printing photocurable resin and a preparation method thereof. By optimizing the components, the prepared photocurable resin has high strength, good waterproof and stain resistance, strong UV resistance, and self-repairability and low shrinkage.
[0015] In the present invention, bisphenol A epoxy acrylate and dipropylene glycol diacrylate are used as photocurable resin base materials. In order to make the prepared resin have low shrinkage, spirocyclic orthocarbonate is introduced as an expansion monomer to improve its shrinkage rate. In order to solve the problem that the addition of the expansion monomer will reduce the rigidity of the polymer network and the comprehensive mechanical properties of the resin, composite zinc oxide whiskers are introduced as a reinforcing component to slow down the expansion of microcracks, thereby improving various properties of the resin.
[0016] In order to improve the uniformity of the zinc oxide whisker dispersion in the resin, the surface of the zinc oxide whisker is first treated with 3-methacryloxypropyltrimethoxysilane to make the surface double-bonded to obtain the pretreated zinc oxide whisker. In order to improve the interface compatibility between the pretreated zinc oxide whisker and the resin base material, free radical polymerization is used to graft hydroxyethyl methacrylate, glycidyl methacrylate and vinyl POSS to synthesize an intermediate preparation with multiple active sites such as epoxy groups and hydroxyl groups. Then, epoxy-hydroxyl ring opening is used to graft hydrophobic benzophenone derivatives to obtain composite zinc oxide whiskers, which are introduced into the resin to greatly improve the water resistance, antibacterial property, ultraviolet resistance and mechanical properties of the resin. The hydrophobic benzophenone derivative is prepared by substitution using 4-hydroxybenzophenone and 2-bromoethanol as raw materials.
[0017] In order to give the resin excellent resistance to mechanical damage, the present invention uses biphenyl bismaleimide, 1,4-dioxane and furfuryl alcohol to synthesize a biphenyl diol containing a DA structure as a chain extender, and chain-extends the prepolymer formed by isophorone diisocyanate and polytetrahydrofuran, and introduces a DA (Diels-Alder) structure with self-repairing properties into the resin to give it excellent self-repairing properties; pentaerythritol triacrylate is introduced as a photocuring active ingredient, a hydrophobic benzophenone derivative is used as a capping agent, and triethylamine is used as a neutralizing agent to prepare a self-repairing polyurethane, wherein the introduction of pentaerythritol triacrylate allows it to participate in the photocuring cross-linking network, improves the complexity of the cross-linking network, and thus improves the water resistance and weather resistance of the resin; and the introduction of the hydrophobic benzophenone derivative not only improves the water resistance of the self-repairing polyurethane, but also gives the self-repairing polyurethane a certain self-crosslinking property, thereby reducing the amount of free radical initiator, improving the photocuring rate and effect, and effectively improving the service life of the finished resin product. DETAILED DESCRIPTION
[0018] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] It should be noted that if the embodiments of the present invention involve directional indications such as up, down, left, right, front, and back, the directional indication is only used to explain a specific posture such as the relative position relationship between the components, the movement status, etc. If the specific posture changes, the directional indication will also change accordingly. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in this field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be considered that such a combination of technical solutions does not exist and is not within the protection scope required by the present invention.
[0020] The technical solution of the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only used to explain the present invention, and are not used to limit the present invention.
[0021] Embodiment 1: A method for preparing a low-shrinkage 3D printing photocurable resin, comprising the following steps: S1: The preparation of self-healing polyurethane includes the following steps: (1) Under a nitrogen atmosphere, 3 g of biphenyl bismaleimide and 20 mL of 1,4-dioxane were mixed, the temperature was raised to 58 °C, and the mixture was stirred until dissolved. 1.8 g of furfuryl alcohol was added, and the mixture was kept warm for 22 h. The mixture was cooled, and 30 mL of ether was added. The mixture was filtered, washed, and dried to obtain a biphenyl diol containing a DA structure. (2) Under a nitrogen atmosphere, 16 g of isophorone diisocyanate, 8 g of polytetrahydrofuran, and 3 drops of dibutyltin dilaurate were mixed, the temperature was raised to 63 ° C, a mixture of 2.4 g of biphenyl diol containing DA structure and 10 mL of acetone was added, and the mixture was kept warm for 2 h. A mixture of 5 g of pentaerythritol triacrylate and 10 mL of acetone was added, and the mixture was kept warm for 1 h. 3 g of hydrophobic benzophenone derivative and 400 ppm of 4-methoxyphenol were added, and the mixture was kept warm for 1 h. The temperature was lowered to 25 ° C, 2 g of triethylamine was added, and the mixture was kept warm for 20 min. The mixture was rotary evaporated and discharged to obtain a self-healing polyurethane. S2: In a nitrogen atmosphere, an initiator, a diluent, a self-healing polyurethane, bisphenol A epoxy acrylate, dipropylene glycol diacrylate, a composite zinc oxide whisker, and a spirocyclic orthocarbonate are ultrasonically mixed and stored away from light to obtain a low-shrinkage 3D printing light-curing resin; The diluent is prepared by mixing isobornyl acrylate and 1,6-hexanediol diacrylate in a mass ratio of 1:1; The initiator is a cationic initiator and a free radical initiator mixed in a mass ratio of 2:1; The raw material composition of the photocurable resin is as follows, by mass: 10 parts of bisphenol A epoxy acrylate, 10 parts of dipropylene glycol diacrylate, 14 parts of self-repairing polyurethane, 0.5 parts of initiator, 12 parts of diluent, 2 parts of composite zinc oxide whisker, and 2 parts of spiro orthocarbonate; The preparation of the spiro orthocarbonate comprises the following steps: Under a nitrogen atmosphere, 0.5 mol of trimethylolpropane allyl ether and 600 mL of toluene were mixed, heated to 115°C and kept warm for 2 h, cooled to 68°C, 0.84 g of p-toluenesulfonic acid was added, cooled to 25°C, 0.25 mol of tetraethyl orthocarbonate was added, heated to 113°C and kept warm for 4 h, cooled to 25°C, 40 mL of triethylamine was added, distilled under reduced pressure, dried, and a mixture of petroleum ether and ethyl acetate in a volume ratio of 9:1 was used as an eluent, and the mixture was purified by silica gel chromatography to obtain spirocyclic orthocarbonate; The preparation of the composite zinc oxide whisker comprises the following steps: 1) 10 mL of deionized water, 10 mL of anhydrous ethanol, 2 mL of formic acid, and 3 g of 3-methacryloxypropyltrimethoxysilane were mixed, 7 g of zinc oxide whiskers were added, the temperature was raised to 98 °C and kept for 4 h, centrifuged, washed, and dried to obtain pretreated zinc oxide whiskers; 2) Under nitrogen atmosphere, 1 g of hydroxyethyl methacrylate, 5 g of glycidyl methacrylate, 6 g of pretreated zinc oxide whiskers, 0.5 g of vinyl POSS, 0.2 g of azobisisobutyronitrile, and 30 mL of N,N-dimethylformamide were mixed, heated to 63°C for 10 h, 20 mL of deionized water was added, and dried to obtain an intermediate preparation; 3) 1.5 g of hydrophobic benzophenone derivative, 3 g of intermediate preparation and 20 mL of chloroform were mixed, 0.6 g of Amberlyst-15 ion exchange resin was added, ultrasonic stirring was performed, the temperature was raised to 55°C and kept in a water bath for 3 h, and then filtered and rotary evaporated to obtain composite zinc oxide whiskers; The preparation of the hydrophobic benzophenone derivative comprises the following steps: in a nitrogen atmosphere, 4 g of 4-hydroxybenzophenone and 8 mL of N,N-dimethylformamide are mixed, 2.7 g of 2-bromoethanol, 5.4 g of potassium carbonate and 4 mL of N,N-dimethylformamide are added, the temperature is raised to 78° C. and kept warm for 24 hours, rotary evaporation is performed, extraction is performed with dichloromethane and saturated brine in sequence, anhydrous magnesium sulfate is added to remove water, suction filtration is performed, rotary evaporation is performed, petroleum ether and ethyl acetate in a volume ratio of 4:1 are used as eluents, purification is performed by silica gel column chromatography, rotary evaporation is performed, and drying is performed to obtain the hydrophobic benzophenone derivative.
[0022] Embodiment 2: A method for preparing a low-shrinkage 3D printing photocurable resin, comprising the following steps: S1: The preparation of self-healing polyurethane includes the following steps: (1) Under a nitrogen atmosphere, 3 g of biphenyl bismaleimide and 20 mL of 1,4-dioxane were mixed, the temperature was raised to 60°C, and the mixture was stirred until dissolved. 1.8 g of furfuryl alcohol was added, and the mixture was kept warm for 23 h. The mixture was cooled, and 30 mL of ether was added. The mixture was filtered, washed, and dried to obtain a biphenyl diol containing a DA structure. (2) Under a nitrogen atmosphere, 16 g of isophorone diisocyanate, 8 g of polytetrahydrofuran, and 3 drops of dibutyltin dilaurate were mixed, the temperature was raised to 63-68 ° C, 2.4 g of a mixture of a biphenyl diol containing a DA structure and 10 mL of acetone was added, and the mixture was kept warm for 2.5 h. A mixture of 5 g of pentaerythritol triacrylate and 10 mL of acetone was added, and the mixture was kept warm for 1.5 h. 3 g of a hydrophobic benzophenone derivative and 400 ppm of 4-methoxyphenol were added, and the mixture was kept warm for 1.5 h. The temperature was lowered to 28 ° C, 2 g of triethylamine was added, and the mixture was kept warm for 25 min. The mixture was rotary evaporated and discharged to obtain a self-healing polyurethane. S2: In a nitrogen atmosphere, an initiator, a diluent, a self-healing polyurethane, bisphenol A epoxy acrylate, dipropylene glycol diacrylate, a composite zinc oxide whisker, and a spirocyclic orthocarbonate are ultrasonically mixed and stored away from light to obtain a low-shrinkage 3D printing light-curing resin; The diluent is prepared by mixing isobornyl acrylate and 1,6-hexanediol diacrylate in a mass ratio of 1:1; The initiator is a cationic initiator and a free radical initiator mixed in a mass ratio of 2:1; The raw material composition of the photocurable resin is as follows, by mass: 13 parts of bisphenol A epoxy acrylate, 13 parts of dipropylene glycol diacrylate, 15 parts of self-repairing polyurethane, 0.8 parts of initiator, 16 parts of diluent, 3 parts of composite zinc oxide whisker, and 2 parts of spiro orthocarbonate; The preparation of the spiro orthocarbonate comprises the following steps: In a nitrogen atmosphere, 0.5 mol of trimethylolpropane allyl ether and 600 mL of toluene were mixed, heated to 115°C and kept warm for 2 h, cooled to 70°C, 0.84 g of p-toluenesulfonic acid was added, cooled to 30°C, 0.25 mol of tetraethyl orthocarbonate was added, heated to 114°C and kept warm for 3.5 h, cooled to 30°C, 40 mL of triethylamine was added, distilled under reduced pressure, dried, and a mixture of petroleum ether and ethyl acetate in a volume ratio of 9:1 was used as an eluent, and the mixture was purified by silica gel chromatography to obtain spirocyclic orthocarbonate; The preparation of the composite zinc oxide whisker comprises the following steps: 1) 10 mL of deionized water, 10 mL of anhydrous ethanol, 2 mL of formic acid, and 3 g of 3-methacryloxypropyltrimethoxysilane were mixed, 7 g of zinc oxide whiskers were added, the temperature was raised to 99 ° C and kept for 3.5 h, centrifuged, washed, and dried to obtain pretreated zinc oxide whiskers; 2) Under nitrogen atmosphere, 1 g of hydroxyethyl methacrylate, 5 g of glycidyl methacrylate, 6 g of pretreated zinc oxide whiskers, 0.5 g of vinyl POSS, 0.2 g of azobisisobutyronitrile, and 30 mL of N,N-dimethylformamide were mixed, heated to 65°C for 9 h, 20 mL of deionized water was added, and dried to obtain an intermediate preparation; 3) 1.5 g of a hydrophobic benzophenone derivative, 3 g of an intermediate preparation, and 20 mL of chloroform were mixed, 0.6 g of Amberlyst-15 ion exchange resin was added, ultrasonic stirring was performed, the temperature was raised to 60°C and kept in a water bath for 2.5 h, and then filtered and rotary evaporated to obtain composite zinc oxide whiskers; The preparation of the hydrophobic benzophenone derivative comprises the following steps: in a nitrogen atmosphere, 4 g of 4-hydroxybenzophenone and 8 mL of N,N-dimethylformamide are mixed, 2.7 g of 2-bromoethanol, 5.4 g of potassium carbonate and 4 mL of N,N-dimethylformamide are added, the temperature is raised to 80° C. and kept for 23 hours, rotary evaporation is performed, extraction is performed with dichloromethane and saturated brine in sequence, anhydrous magnesium sulfate is added to remove water, suction filtration is performed, rotary evaporation is performed, petroleum ether and ethyl acetate in a volume ratio of 4:1 are used as eluents, purification is performed by silica gel column chromatography, rotary evaporation is performed, and drying is performed to obtain the hydrophobic benzophenone derivative.
[0023] Embodiment 3: A method for preparing a low-shrinkage 3D printing photocurable resin, comprising the following steps: S1: The preparation of self-healing polyurethane includes the following steps: (1) Under a nitrogen atmosphere, 3 g of biphenyl bismaleimide and 20 mL of 1,4-dioxane were mixed, the temperature was raised to 62 °C, and the mixture was stirred until dissolved. 1.8 g of furfuryl alcohol was added, and the mixture was kept warm for 24 h. The mixture was cooled, and 30 mL of ether was added. The mixture was filtered, washed, and dried to obtain a biphenyl diol containing a DA structure. (2) Under a nitrogen atmosphere, 16 g of isophorone diisocyanate, 8 g of polytetrahydrofuran, and 3 drops of dibutyltin dilaurate were mixed, the temperature was raised to 68 ° C, a mixture of 2.4 g of biphenyl diol containing DA structure and 10 mL of acetone was added, and the mixture was kept warm for 3 h. A mixture of 5 g of pentaerythritol triacrylate and 10 mL of acetone was added, and the mixture was kept warm for 2 h. 3 g of hydrophobic benzophenone derivative and 400 ppm of 4-methoxyphenol were added, and the mixture was kept warm for 2 h. The temperature was lowered to 35 ° C, 2 g of triethylamine was added, and the mixture was kept warm for 30 min. The mixture was rotary evaporated and discharged to obtain a self-healing polyurethane. S2: In a nitrogen atmosphere, an initiator, a diluent, a self-healing polyurethane, bisphenol A epoxy acrylate, dipropylene glycol diacrylate, a composite zinc oxide whisker, and a spirocyclic orthocarbonate are ultrasonically mixed and stored away from light to obtain a low-shrinkage 3D printing light-curing resin; The diluent is prepared by mixing isobornyl acrylate and 1,6-hexanediol diacrylate in a mass ratio of 1:1; The initiator is a cationic initiator and a free radical initiator mixed in a mass ratio of 2:1; The raw material composition of the photocurable resin is as follows, by mass: 15 parts of bisphenol A epoxy acrylate, 15 parts of dipropylene glycol diacrylate, 16 parts of self-repairing polyurethane, 1 part of initiator, 17 parts of diluent, 5 parts of composite zinc oxide whisker, and 2 parts of spiro orthocarbonate; The preparation of the spiro orthocarbonate comprises the following steps: In a nitrogen atmosphere, 0.5 mol of trimethylolpropane allyl ether and 600 mL of toluene are mixed, heated to 115°C and kept for 2 hours, cooled to 68-72°C, 0.84 g of p-toluenesulfonic acid is added, cooled to 25-35°C, 0.25 mol of tetraethyl orthocarbonate is added, heated to 113-115°C and kept for 3-4 hours, cooled to 25-35°C, 40 mL of triethylamine is added, distilled under reduced pressure, dried, and a mixture of petroleum ether and ethyl acetate in a volume ratio of 9:1 is used as an eluent, and purified by a silica gel chromatography column method to obtain spirocyclic orthocarbonate; The preparation of the composite zinc oxide whisker comprises the following steps: 1) Mix 10 mL of deionized water, 10 mL of anhydrous ethanol, 2 mL of formic acid, and 3 g of 3-methacryloxypropyltrimethoxysilane, add 7 g of zinc oxide whiskers, heat to 98-100 ° C for 3-4 hours, centrifuge, wash, and dry to obtain pretreated zinc oxide whiskers; 2) Under nitrogen atmosphere, 1 g of hydroxyethyl methacrylate, 5 g of glycidyl methacrylate, 6 g of pretreated zinc oxide whiskers, 0.5 g of vinyl POSS, 0.2 g of azobisisobutyronitrile, and 30 mL of N,N-dimethylformamide were mixed, heated to 68°C for 8 h, 20 mL of deionized water was added, and dried to obtain an intermediate preparation; 3) 1.5 g of a hydrophobic benzophenone derivative, 3 g of an intermediate preparation, and 20 mL of chloroform were mixed, 0.6 g of Amberlyst-15 ion exchange resin was added, ultrasonic stirring was performed, the temperature was raised to 65°C and kept in a water bath for 3 h, and then filtered and rotary evaporated to obtain composite zinc oxide whiskers; The preparation of the hydrophobic benzophenone derivative comprises the following steps: in a nitrogen atmosphere, 4 g of 4-hydroxybenzophenone and 8 mL of N,N-dimethylformamide are mixed, 2.7 g of 2-bromoethanol, 5.4 g of potassium carbonate and 4 mL of N,N-dimethylformamide are added, the temperature is raised to 82° C. and kept for 22 hours, rotary evaporation is performed, extraction is performed with dichloromethane and saturated brine in sequence, anhydrous magnesium sulfate is added to remove water, suction filtration is performed, rotary evaporation is performed, petroleum ether and ethyl acetate in a volume ratio of 4:1 are used as eluents, purification is performed by silica gel column chromatography, rotary evaporation is performed, and drying is performed to obtain the hydrophobic benzophenone derivative.
[0024] Comparative Example 1: Taking Example 3 as the control group, zinc oxide whiskers were used to replace the composite zinc oxide whiskers, and other processes were normal.
[0025] Comparative Example 2: Example 3 was used as a control group, in which no hydrophobic benzophenone derivative was prepared, and other processes were normal.
[0026] Sources of raw materials used (for demonstration purposes only): Amberlyst-15 ion exchange resin Y52434: Shanghai Yuanye Biotechnology Co., Ltd.; zinc oxide whiskers (5µm): Hefei Aijia New Materials Technology Co., Ltd.; cationic initiator UVI-6992: Hubei Mackays Fine Chemical Technology Co., Ltd.; p-Toluenesulfonic acid (99%): Shandong Yukang Chemical Co., Ltd.; bisphenol A epoxy acrylate (industrial grade, 99%): Wuhan Jixin Yibang Biotechnology Co., Ltd.; free radical initiator 819, dipropylene glycol diacrylate (98%): Hubei Zhenbo Chemical Co., Ltd.; biphenyl bismaleimide (13676-54-5, 99%): Kangdis Chemical (Hubei) Co., Ltd.; 1,4-dioxane D116157, furfuryl alcohol F110604, isophorone diisocyanate I109582, dibutyltin dilaurate D100274, polytetrahydrofuran P141386, dibutyltin dilaurate D100274 , Pentaerythritol triacrylate P492035, 4-methoxyphenol M170858, triethylamine T103285, isobornyl acrylate I157699, 1,6-hexanediol diacrylate H102721, trimethylolpropane allyl ether T487225, tetraethyl orthocarbonate T107475, 3-methacryloyloxypropyl trimethoxysilane S111153, hydroxyethyl methacrylate H103044, methyl acrylate Glycidyl acrylate G106686, vinyl POSSP102212, azobisisobutyronitrile A434183, N,N-dimethylformamide D111999, 4-hydroxybenzophenone H108575, 2-bromoethanol B111177: Aladdin reagent; ether, acetone, toluene, petroleum ether, ethyl acetate, ethanol, formic acid, chloroform, potassium carbonate, dichloromethane, saturated brine, anhydrous magnesium sulfate, analytical grade: Sinopharm Group reagent.
[0027] Performance test: The resins prepared in the examples and comparative examples were tested: Sample molding: 150 g of resin was placed on the work platform of the light-curing 3D printer, the printing layer thickness was 50 μm, the exposure time was 15 s, and ultraviolet light (wavelength was 365 nm) was used for curing, layer by layer, and the sample was prepared by stacking and molding with a layer thickness of 50 μm; Curing shrinkage: The density of the resin before and after curing was measured using an electronic density meter at a temperature of 25°C. The curing shrinkage Δ= (ρ2-ρ1) / ρ2×100%; Tensile strength: The sample size was 20 mm long, 2 mm wide, and 2 mm thick. It was tested using a universal testing machine at a tensile rate of 50 mm / min; Self-healing property: The sample size was 20 mm long, 20 mm wide, and 2 mm thick. A scratch of 1 mm long, 2 µm wide, and 1 mm deep was made on it. The scratch was then kept at 150°C for 2 hours. The scratch of the material was observed under a microscope. The self-healing rate was (L 初始 -L 现有) / L 初始 ×100%; Water resistance: The sample size is 20mm long, 20mm wide, and 2mm thick, weighed and recorded as m0, soaked in deionized water at 100°C for 12h, taken out and dried and weighed as m1, and the water absorption rate is m1 / m0×100%; UV resistance: irradiated with 365nm light for 72h, and the tensile strength is measured again. The change rate of tensile strength is below 2% including 2% for excellent performance, otherwise it is unqualified; the results are shown in Table 1; Table 1 The present invention provides a low-shrinkage 3D printing photocurable resin and a preparation method thereof. By optimizing the components, the prepared photocurable resin has high strength, good waterproof and stain resistance, and self-healing properties and low shrinkage. In Table 1, / indicates that the item has not been tested.
[0028] By comparing Example 3 with Comparative Example 1 and Comparative Example 2, it can be seen that in order to improve the uniformity of the dispersion of zinc oxide whiskers in the resin, the surface of the zinc oxide whiskers is first treated with 3-methacryloxypropyltrimethoxysilane to make the surface double-bonded to obtain pretreated zinc oxide whiskers. In order to improve the interfacial compatibility between the pretreated zinc oxide whiskers and the resin base material, free radical polymerization is used to graft hydroxyethyl methacrylate, glycidyl methacrylate, and vinyl POSS to synthesize an intermediate preparation with multiple active sites such as epoxy groups and hydroxyls, and then epoxy-hydroxyl ring opening is used to graft hydrophobic benzophenone derivatives to obtain composite zinc oxide whiskers, which are introduced into the resin to greatly improve the water resistance, antibacterial property, UV resistance and mechanical properties of the resin; wherein the hydrophobic benzophenone derivative is prepared by substitution using 4-hydroxybenzophenone and 2-bromoethanol as raw materials.
[0029] By comparing Example 3 with Comparative Examples 1 and 2, it can be seen that in order to give the resin excellent resistance to mechanical damage, the present invention uses biphenyl bismaleimide, 1,4-dioxane, and furfuryl alcohol to synthesize a biphenyl diol containing a DA structure as a chain extender, and the prepolymer formed by isophorone diisocyanate and polytetrahydrofuran is chain extended, and a DA (Diels-Alder) structure with self-healing properties is introduced into the resin to give it excellent self-healing properties; pentaerythritol triacrylate is introduced as a photocurable active ingredient , a self-healing polyurethane was prepared using a hydrophobic benzophenone derivative as a capping agent and triethylamine as a neutralizing agent, wherein the introduction of pentaerythritol triacrylate enabled it to participate in the photocuring cross-linking network, thereby increasing the complexity of the cross-linking network and thus improving the water resistance and weather resistance of the resin; while the introduction of the hydrophobic benzophenone derivative not only improves the water resistance of the self-healing polyurethane, but also gives the self-healing polyurethane a certain self-cross-linking property, thereby reducing the amount of free radical initiator used, increasing the photocuring rate and effect, and effectively increasing the service life of the finished resin product.
[0030] The above descriptions are only embodiments of the present invention and are not intended to limit the patent scope of the present invention. All equivalent structural changes made using the present invention specification under the inventive concept of the present invention, or direct / indirect applications in other related technical fields, are included in the patent protection scope of the present invention.
Claims
1. A method for preparing a low-shrinkage 3D printing photocurable resin, characterized in that: The following steps are involved: S1: Preparation of self-healing polyurethane using biphenyl diols containing DA structure and hydrophobic benzophenone derivatives; S2: In a nitrogen atmosphere, an initiator, a diluent, a self-healing polyurethane, bisphenol A epoxy acrylate, dipropylene glycol diacrylate, a composite zinc oxide whisker, and a spirocyclic orthocarbonate are ultrasonically mixed and stored away from light to obtain a low-shrinkage 3D printing photocurable resin.
2. The method for preparing a low-shrinkage 3D printing photocurable resin according to claim 1, characterized in that: The diluent is prepared by mixing isobornyl acrylate and 1,6-hexanediol diacrylate in a mass ratio of 1:
1.
3. The method for preparing a low-shrinkage 3D printing photocurable resin according to claim 1, characterized in that: The initiator is a cationic initiator and a free radical initiator mixed in a mass ratio of 2:
1.
4. The method for preparing a low-shrinkage 3D printing photocurable resin according to claim 1, characterized in that: The raw material composition of the photocurable resin is as follows, in parts by mass: 10-15 parts of bisphenol A epoxy acrylate, 10-15 parts of dipropylene glycol diacrylate, 14-16 parts of self-repairing polyurethane, 0.5-1 parts of initiator, 12-17 parts of diluent, 2-5 parts of composite zinc oxide whiskers, and 2 parts of spirocyclic orthocarbonate.
5. The method for preparing a low-shrinkage 3D printing photocurable resin according to claim 1, characterized in that: The preparation of the spirocyclic orthocarbonate comprises the following steps: In a nitrogen atmosphere, trimethylolpropane allyl ether and toluene are mixed, heated to 115°C and kept warm for 2 hours, cooled to 68-72°C, p-toluenesulfonic acid is added, cooled to 25-35°C, tetraethyl orthocarbonate is added, heated to 113-115°C and kept warm for 3-4 hours, cooled to 25-35°C, triethylamine is added, distilled under reduced pressure, dried, and purified by silica gel chromatography using a mixture of petroleum ether and ethyl acetate in a volume ratio of 9:1 as an eluent to obtain spirocyclic orthocarbonate.
6. The method for preparing a low-shrinkage 3D printing photocurable resin according to claim 1, characterized in that: The preparation of the composite zinc oxide whisker comprises the following steps: 1) Mix deionized water, anhydrous ethanol, formic acid and 3-methacryloxypropyltrimethoxysilane, add zinc oxide whiskers, heat to 98-100°C and keep warm for 3-4 hours, centrifuge, wash and dry to obtain pretreated zinc oxide whiskers; 2) Under a nitrogen atmosphere, hydroxyethyl methacrylate, glycidyl methacrylate, pretreated zinc oxide whisker, vinyl POSS, azobisisobutyronitrile, and N,N-dimethylformamide are mixed, heated to 63-68° C. for 8-10 hours, deionized water is added, and dried to obtain an intermediate preparation; 3) Mix the hydrophobic benzophenone derivative, the intermediate preparation and chloroform, add Amberlyst-15 ion exchange resin, stir ultrasonically, heat to 55-65°C in a water bath for 2-3 hours, filter and rotary evaporate to obtain composite zinc oxide whiskers.
7. The method for preparing a low-shrinkage 3D printing photocurable resin according to claim 1, characterized in that: The preparation of the self-repairing polyurethane comprises the following steps: (1) Under a nitrogen atmosphere, biphenyl bismaleimide and 1,4-dioxane are mixed, heated to 58-62°C, stirred until dissolved, furfuryl alcohol is added, kept warm for 22-24 hours, cooled, ether is added, filtered, washed, and dried to obtain a biphenyl diol containing a DA structure; (2) Under a nitrogen atmosphere, isophorone diisocyanate, polytetrahydrofuran and dibutyltin dilaurate are mixed, the temperature is raised to 63-68°C, a mixture of biphenyl diol containing a DA structure and acetone is added, the temperature is kept for 2-3 hours, a mixture of pentaerythritol triacrylate and acetone is added, the temperature is kept for 1-2 hours, a hydrophobic benzophenone derivative and 4-methoxyphenol are added, the temperature is kept for 1-2 hours, the temperature is lowered to 25-35°C, triethylamine is added, the temperature is kept for 20-30 minutes, and the material is discharged by rotary evaporation to obtain a self-healing polyurethane.
8. The method for preparing a low-shrinkage 3D printing photocurable resin according to claim 7, characterized in that: The mass ratio of isophorone diisocyanate, polytetrahydrofuran, biphenyl diol containing DA structure, pentaerythritol triacrylate and hydrophobic benzophenone derivative is 16:8:2.4:5:
3.
9. The method for preparing a low-shrinkage 3D printing photocurable resin according to claim 1, characterized in that: The preparation of the hydrophobic benzophenone derivative comprises the following steps: under a nitrogen atmosphere, 4-hydroxybenzophenone and N,N-dimethylformamide are mixed, 2-bromoethanol, potassium carbonate and N,N-dimethylformamide are added, the temperature is raised to 78-82° C. and kept warm for 22-24 hours, rotary evaporation is performed, extraction is performed with dichloromethane and saturated brine in sequence, anhydrous magnesium sulfate is added to remove water, suction filtration is performed, rotary evaporation is performed, petroleum ether and ethyl acetate in a volume ratio of 4:1 are used as eluent, purification is performed by silica gel column chromatography, rotary evaporation is performed, and drying is performed to obtain the hydrophobic benzophenone derivative.
10. A low shrinkage 3D printing photocurable resin, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 9.